Disability and the Right to Have Rights - Siebers, Tobin (Disability Studies Quarterly, 2007)
A major debate over human rights discourse concerns whether human rights should be guaranteed by the nation-state based on citizenship or whether they should be guaranteed internationally on the basis of the status of the rights-bearing person as human. This essay intervenes in this debate, via an analysis of Hannah Arendt's idea of the right to have rights, to argue that disability, as a critical indicator of universal human frailty, should provide the basis for international human rights.